Analysis of time delay difference due to parametric mismatch in matched filter channels - Julian, Pedro Marcelo (2014)
This paper presents an analysis of the time delay difference between the outputs of two matched filter channels, in the presence of parametric mismatch. A theorem for computing the cross-correlation value between two signals is developed. From the cross-correlation theorem, expressions are developed that estimate the effect of parametric mismatch in the differential time delay (DTD) for filters of arbitrary type and order and input signals of arbitrary form. The accuracy of these expressions is simulated and then demonstrated experimentally using a carefully designed setup. Filter design considerations that attempt to minimize spurious DTD in high-precision time delay estimation systems are presented.